ANALISA TREN PEMANFAATAN CELEBRITY ENDORSEMENT: SEBUAH ULASAN LITERATUR SISTEMATIS (Jurnal Kajian Media, 2023)
This systematic literature review aims to analyze studies on the use of endorsement marketing by celebrities. The data comes from several sources from Crossref collected between 2020 and 2022. Keywords used include "Social Media Marketing," "Endorsement Marketing," and "Celebrity Endorsement." From this search process, fifteen articles related to the topic were found. The results show that the source attractiveness and credibility model is a model that brands trust to have an effective impact because the determining factor for the success of celebrity endorsement lies in the source or messenger, namely the celebrity. Celebrity endorsement through celebrity social media accounts is increasingly popular as a social media marketing strategy because it influences buying behavior. Keywords: social media marketing, endorsement, celebrity endorsement.